The Clinical Effect of Repetitive Transcranial Magnetic Stimulation on the Disturbance of Consciousness in Patients in a Vegetative State - Zhang, Xiao-Hua; Han, Ping; Zeng, Yuan-Yuan; Wang, Yu-Long; Lv, Hui-Lan (Frontiers in Neuroscience, 2021)
Objective: To explore the effect of a combination of repetitive transcranial magnetic stimulation (rTMS) and conventional rehabilitation on the recovery of consciousness in patients in a persistent vegetative state (PVS). Methods: A total 48 patients in a PVS were randomly divided into treatment group and control group. Patients in the treatment group were treated with rTMS to stimulate the dorsolateral prefrontal cortex, and patients in the control group were treated with false stimulation. All patients were evaluated using scales and neuroelectrophysiological assessment before treatment, after 30 days of treatment, and after 60 days of treatment. Results: In terms of the Coma Recovery Scale Revised (CRS-R) and the electroencephalogram (EEG) grading indexes, the treatment group were significantly higher than those of the control group after 30 days and 60 days of treatment. The average difference in the three measurements between the two groups before treatment, at 30 days, and at 60 days was 0.04, 1.54, and 2.09 for CRS-R and 0.08, -0.83, and -0.62 for EEG, respectively. The latency periods of each wave of the BAEP in the treatment group were shorter than those in the control group after 30 days and 60 days of treatment. In both groups, the BAEP scores after 30 days of treatment were significantly higher than the scores before treatment, and the scores after 60 days of treatment were higher than the scores after 30 days. Conclusion: rTMS has the effect of assisting with the recovery of consciousness function in patients in a PVS.